2018
DOI: 10.1063/1.5012844
|View full text |Cite
|
Sign up to set email alerts
|

Absolute cross section measurements for the scattering of low- and intermediate-energy electrons from PF3. II. Inelastic scattering of vibrational and electronic excitations

Abstract: As a sequel paper to our study of the elastic scattering for electron collisions with phosphorus trifluoride, PF molecules, we report absolute inelastic differential and integral cross sections (DCS and ICS) of vibrational excitations for the compound fundamental vibrational modes v (v + v), v (v + v), and their sum in the impact energy range of 2.0-10 eV and over a scattering angle range of 20°-130°. The measured angular distributions of scattered electron intensities for the present inelastic scattering are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Details on inelastic processes, especially vibrational and electronic excitations, for the e + PF 3 collisional system will be discussed in a sequel paper (Part II). 14…”
Section: Discussionmentioning
confidence: 99%
“…Details on inelastic processes, especially vibrational and electronic excitations, for the e + PF 3 collisional system will be discussed in a sequel paper (Part II). 14…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of electron scattering from PF 3 have included the calculation of the total elastic and total inelastic (ionisation and excitation) cross sections (0.15 to 5000 eV), 23 measurement and calculation of elastic differential cross sections between 2.0-200 eV, 24 measurement and calculation of integral and differential vibrational cross sections (2.0-10 eV), 25 measurement of ion appearance energies and relative ion intensities at 70 eV, 26,27 measurement of experimental absolute total scattering cross sections (0.5 to 370 eV) 28 and calculations of partial differential ionisation cross sections at 100 eV and 200 eV. 29 Photoionisation of PF 3 has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The microwave rotational spectrum has also been rather well studied [17,27,[33][34][35][36]. Very recently a study of vibrational and electronic inelastic electron scattering on PF 3 has been reported [37].…”
Section: Introductionmentioning
confidence: 99%